The Washback Effect of Task-Based Language Assessment on ESL Teachers and Students in a Low-Stakes Instructional Context in Egypt - Makkar, Marina Alfonse (AUC Knowledge Fountain, 2026)
Washback is the effect that assessment exerts on teaching and learning, a phenomenon mediated by learner interpretations, teacher practices, and contextual conditions. Within this perspective, Task-Based Language Assessment (TBLA) emphasizes authentic communication and meaningful language use, positioning tasks as the primary means of eliciting evidence of language ability. While TBLA has the potential to generate positive washback when aligned with instructional goals, its effects remain under-researched in non-traditional educational settings. This study investigated the washback effects of TBLA in a low-stakes English-language instructional context at a school of continuing education (SCE) in an Egyptian private university. Data were collected from 55 teachers and 112 students through questionnaires, supplemented by semi-structured interviews with five teachers and five students, to examine both intended washback and stakeholders' perceptions. The findings indicated that TBLA promoted meaningful language use, learner engagement, and communicative teaching practices. Generally positive perceptions were reported by both teachers and students, particularly regarding the role of interaction and feedback in supporting learning. However, the results also revealed that washback was mediated by learners' varied understandings of assessment demands, inconsistencies in teacher implementation, and limited institutional collaboration. The washback of TBLA in low-stakes contexts operated through contextual variations in feedback, self-reflection, and classroom engagement practices, encouraging more authentic communication and meaningful language development without being associated with high-stakes pressure. The findings further suggested that the persistence of traditional, test-oriented educational ideologies in Egypt continues to constrain the effective implementation of task-based frameworks. These results highlight the need for targeted teacher training and institutional support to bridge the gap between assessment design and classroom reality.